2020
DOI: 10.21203/rs.3.rs-43489/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro inactivation of SARS-CoV-2 by commonly used disinfection products and methods

Abstract: Background Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection is currently a global pandemic, and there is a lack of laboratory studies targeting pathogen resistance.Objective To investigate the effect of selected disinfection products and methods on the inactivation of SARS-CoV-2.Methods We used quantitative suspension testing to evaluate the effectiveness of the disinfectant/method.Results Available chlorine of 250 mg/L, 500 mg/L, and 1000 mg/L required 20 min, 5 min, and 0.5 min to effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…While only a single device was tested in this study, a variety of UV inactivation studies have been published focusing on SARS-CoV-2 and other coronaviruses using different wavelengths and environmental conditions [ 30 , 31 , 41 , 42 , 43 , 44 , 45 ]. In contrast to the broad-spectrum UV device tested here, most UV devices that have been tested for efficacy against SARS-CoV-2 produce constant, non-pulsed UV-C (222–300 nm) light exclusively [ 28 , 30 , 31 , 32 , 33 ]. One other study has focused on a UV device that produces pulsed UV from high intensity xenon lamps; however, the wavelengths produced by the device were not reported [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While only a single device was tested in this study, a variety of UV inactivation studies have been published focusing on SARS-CoV-2 and other coronaviruses using different wavelengths and environmental conditions [ 30 , 31 , 41 , 42 , 43 , 44 , 45 ]. In contrast to the broad-spectrum UV device tested here, most UV devices that have been tested for efficacy against SARS-CoV-2 produce constant, non-pulsed UV-C (222–300 nm) light exclusively [ 28 , 30 , 31 , 32 , 33 ]. One other study has focused on a UV device that produces pulsed UV from high intensity xenon lamps; however, the wavelengths produced by the device were not reported [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While chemical disinfectants and alcohols are effective methods of inactivating SARS-CoV-2 in most circumstances, disinfection of large spaces using these methods is a laborious process requiring close contact with potentially contaminated surfaces [ 25 , 26 , 27 , 28 ]. UV light has long been established as an effective and direct method for the inactivation of enveloped viruses [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, contaminated surfaces and solutions are a reservoir for transmission through fomites, meaning effective hygiene and environmental decontamination is crucial in helping to prevent the spread of COVID-19 [11,12]. Disinfectant solutions of 75 % ethanol and 10 % sodium hypochlorite are able to reduce SARS-CoV-2 titre by at least 2.0 log 10 TCID 50 ml −1 and 3.25 log 10 TCID 50 ml −1 , respectively, within 5 min [10,13]. However, the World Health Organization (WHO) has recommended diluting household bleach 1 : 100 to reduce irritation to the user and contact times of 10 to 60 min to disinfect surfaces and when immersing items [14].…”
Section: Discussionmentioning
confidence: 99%
“…van Doremalen et al (2020) found the SARS-COV-2 viruses on the outer surface of a face mask for up to 7 days [10]. According to WHO's interim guidance to clean and disinfect environment in the context of SARS-COV-2 virus, disinfectant products containing alcohol 70 -90%, chlorine-based at 0.1% v/v and 0.5% v/v and hydrogen peroxide at > 0.5% v/v can be used to combat SARS-COV-2 virus transmission [11,12]. Since no report was found about the influence of the disinfection step on recycled plastic pellets' physical and chemical properties, we report the physicochemical characteristic of the filtering layer from disposable mask before and after the recycling process.…”
Section: Introductionmentioning
confidence: 99%